2022
DOI: 10.3390/jcdd9050129
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Clinical and Morphological Factors on Long-Term Mortality in Patients with Myocardial Bridge

Abstract: Although myocardial bridging (MB) has been intensively investigated using different methods, the effect of bridge morphology on long-term outcome is still doubtful. We aimed at describing the anatomical differences in coronary angiography between symptomatic and non-symptomatic LAD myocardial bridges and to investigate the influence of clinical and morphological factors on long-term mortality. In our retrospective, long-term, single center study we found relevant MB on the left anterior descendent (LAD) corona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0
3

Year Published

2023
2023
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 24 publications
0
5
0
3
Order By: Relevance
“…Vanker et al observed IMLAD in 293 of 1,349 patients undergoing CABG and reported a prevalence of 21.7%, while other similar studies reported lower prevalence rates ranging between 1-2%. 2,6,9,10 Our study demonstrates that patients with IM-LADs have comparable early and mid-term outcomes to the matched control group. Cross-clamp and CPB times did not differ significantly between groups, despite the additional time required to locate the LAD which in turn reflects the comparable postoperative outcomes in both groups.…”
Section: Discussionmentioning
confidence: 56%
“…Vanker et al observed IMLAD in 293 of 1,349 patients undergoing CABG and reported a prevalence of 21.7%, while other similar studies reported lower prevalence rates ranging between 1-2%. 2,6,9,10 Our study demonstrates that patients with IM-LADs have comparable early and mid-term outcomes to the matched control group. Cross-clamp and CPB times did not differ significantly between groups, despite the additional time required to locate the LAD which in turn reflects the comparable postoperative outcomes in both groups.…”
Section: Discussionmentioning
confidence: 56%
“…Saját retrospektív kutatásunkban [22] a myocardialis izomhíd koronarográfia során meghatározható morfológiai jellemzőit kerestük, amelyek angina pectorishoz vezettek. Azt is vizsgáltuk, hogy az így meghatározott morfológiai faktorok befolyásolják-e a hosszú távú túlélést.…”
Section: Terápiaunclassified
“…Globally, these findings imply that population diversity and inclusion in analyses always matter, as numbers keep varying both on autopsy [14][15][16][17] and angiogram. [18][19][20][21] MBs tend to be localized more in the left system, and Loukas et al 15 found it to be coronary artery dominance-dependent in their sample; however, MBs over the right coronary artery are also described, 22 while concomitant presence with a quadricuspid aortic valve, 23 transposition of great arteries, 24 hamartoma, 25 Takotsubo and spontaneous coronary artery dissection 26,27 have recently been reported.…”
mentioning
confidence: 98%
“…Como as ferramentas de diagnóstico avançaram substancialmente nas últimas duas décadas, 28 a avaliação de pacientes PM que se apresentaram a um cardiologista permanece em função da logística local 17 , 20 , 29 - 32 e da experiência em manejo de longo prazo. No entanto, antes de chegarmos à decisão de tratamento, o quando, o onde e como as PMs se tornam amigas, inimigas ou ambas, de nossos pacientes em função de seu papel na aterogênese permanece o ponto central.…”
unclassified
See 1 more Smart Citation